2017
DOI: 10.1248/bpb.b17-00386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascorbyl-2-phosphate Magnesium on Human Keratinocyte Toxicity and Pathological Changes by Sorafenib

Abstract: Hand-foot skin reaction is recognized as one of the most common adverse events related to multiple tyrosine kinase inhibitors, but an effective prevention method has not been identified. The chief aim of this study was to find a mechanism-based preventive method for the skin toxicity induced by sorafenib using vitamin C derivatives. The effects of ascorbyl-2-phosphate magnesium (P-VC-Mg) on the molecular and pathological changes induced by sorafenib were investigated in human keratinocyte HaCaT cells. The cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…We have reported the effects of ascorbic acid derivatives on keratinocyte toxicity induced by multiple-TKIs in vitro [13]. We verified these effects using an animal-testing alternative, consisting of a reconstructed human epidermal model in vitro.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We have reported the effects of ascorbic acid derivatives on keratinocyte toxicity induced by multiple-TKIs in vitro [13]. We verified these effects using an animal-testing alternative, consisting of a reconstructed human epidermal model in vitro.…”
Section: Discussionmentioning
confidence: 86%
“…We recently reported on ascorbyl-2-phosphate magnesium (P-VC-Mg), a highly permeable ascorbic acid derivative; we found that it could relieve multiple-TKI-induced keratinocyte growth inhibition and pathological changes in human keratinocyte cells in a 3D skin model, mediating signal transducer and activator of transcription 3 phosphorylation levels [13,14]. This report suggested that specific ascorbic acid derivatives can prevent multiple-TKI-induced HFSR.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study suggested that an 3D epidermal model treated with multiple TKIs is applicable to the study of HFSR in vitro model using pathology images. 14 is associated with the functional mechanism of sunitinib. 15,16 This is the first report to identify sunitinib-induced molecular changes in cornifying factors in human keratinocytes in a 3D epidermal model.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that, in a 3D epidermal model, sunitinib decreased the levels of cornifying factors related to normal keratinization. Our previous study suggested that an 3D epidermal model treated with multiple TKIs is applicable to the study of HFSR in vitro model using pathology images 14 . These changes in expression might be regulated by the MAPK signalling pathway, which is associated with the functional mechanism of sunitinib 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a Japanese doctor, Yamamoto ( 59 ), is now leading a clinical study that aims to put forward the application of ascorbyl-2-phosphate magnesium (P-VC-Mg), a cosmetic product, for the treatment of HFSR. Although no results were available yet, his preliminary experimental data ( 60 ) have indicated that this highly permeable ascorbic acid derivative could confront against sorafenib-induced hyperproliferation of keratinocytes in a 3D skin model.…”
Section: Histology Of Hfsrmentioning
confidence: 99%